2007
DOI: 10.4102/hsag.v12i2.245
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of mothers who lost a baby during pregnancy

Abstract: The purpose of this study was to explore and describe the experiences of mothers who lost a baby during pregnancy and care given by doctors and midwives during this period. <b>Opsomming</b> Die doel van die studie was om die ervaring van moeders met betrekking tot die dood van ‘n baba tydens swangerskap te verken en te beskryf, asook die versorging wat hulle van vroedvroue en dokters gedurende die periode ontvang het. *Please note: This is a reduced version of the abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Positive community support, as opposed to stigmatisation and blame, can improve bereavement experience . (FES 68%): Women who experienced emotional and material support from society, including family, friends, religious, and peer support groups reported lower perinatal grief and depression scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive community support, as opposed to stigmatisation and blame, can improve bereavement experience . (FES 68%): Women who experienced emotional and material support from society, including family, friends, religious, and peer support groups reported lower perinatal grief and depression scores.…”
Section: Resultsmentioning
confidence: 99%
“…Women's experience of grief has multiple manifestations often unrecognised by the healthcare community and wider society . (FES 65%): Women across all cultures experienced grief that manifested as physical symptoms, such as fatigue and pain, and emotionally, in the form of sadness, anxiety, guilt, confusion, and anger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grief following miscarriage, stillbirth or neonatal death is particularly susceptible to being disenfranchised, as only parents have “known” the baby, felt it move, or observed it by ultrasound. Modiba and Nolte (2007:4) reported that mothers who suffered perinatal loss expressed the wish that people should acknowledge their losses, be considerate and sensitive, be sympathetic listeners and offer emotional support. This contrastswith typical social norms, where the loss is considered of lesser gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Parents who have experienced perinatal loss may feel hardship and face difficult time during this period. Modiba and Nolte (2007) reported that mothers with perinatal loss expressed their wishes that people should acknowledge their losses, be considerate and sensitive, and give them a listening ear and emotional support. It was also mentioned in the study that health workers should provide the mothers with appropriate support.…”
Section: Introductionmentioning
confidence: 99%